FAMILY ECONOMIC LEVEL AND IMPLEMENTATION OF ISLAMIC BASIC EDUCATION IN AL-HUSNA PRINCESS DORMS - Imam Tabroni; Ade Halimah; Taufik Ilham; Lida Trixivania (Pusat Riset dan Inovasi Nasional, 2022)
This research was conducted to determine how big the relationship between the role of the family in providing Islamic education to children's abilities and to find out how big the ability of parents to provide basic Islamic education to their children. The method used in this research is to use quantitative methods using a correlation approach. We took samples from the parents of the students of the Al-Husna female dormitory. The results of this study state that there is a correlation between the ability of families to basic Islamic education in children. This is based on the calculation of r + 0.611 which is then consulted with the price of